If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (sqrt) * 2 + -1x = 42.5 Reorder the terms for easier multiplication: 2qrst + -1x = 42.5 Solving 2qrst + -1x = 42.5 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add 'x' to each side of the equation. 2qrst + -1x + x = 42.5 + x Combine like terms: -1x + x = 0 2qrst + 0 = 42.5 + x 2qrst = 42.5 + x Divide each side by '2rst'. q = 21.25r-1s-1t-1 + 0.5r-1s-1t-1x Simplifying q = 21.25r-1s-1t-1 + 0.5r-1s-1t-1x
| X-3+3-x= | | G(f-a-b)=g(F-A-(1000-b)) | | 8[x+7]-6=18 | | x^2=3y^2 | | 32x=27x-1 | | logx(89)=5 | | 4[a-3]+12=32 | | X+.66666667x=135 | | P-1(p-2)=p | | 9x-1=-x-1 | | (2lnx-ln^2x)/x2=0 | | 15x+1=-4+20 | | -1(n-1)=-2(n+3) | | 4/7(10360)=280 | | (15,-11)y=3/5x-8 | | x^2+49-14x= | | 34/61*34/61*34/61*34/61 | | Y+3.25=8.50 | | 34/61^4 | | 5[x-2]=-5 | | 5sin^2(x)cosx=0 | | 16[x-8]=-16 | | 6[x+5]=18 | | 2(10x+8)-70=5(2x-20)+76 | | -3(n-2)=-4n-1 | | 7-14=5y-4y+6 | | (x^6y^3)^1/3 | | x^2+1-2x= | | 9x+13x-2x=15-10 | | -2/3×-15= | | 8a-6a+a=7-19 | | -2/3×-15 |